Potensi Ekstrak Tanaman Lenca (Solanum Nigrum) Dan Biji Pepaya (Carica Papaya) Terhadap Mortalitas Larva Aedes Sp Dan Culex Sp Instar IV - Intan Kurniawati Pramitaningrum; Elfira Maya Sari (LPPM STIKES Guna Bangsa, 2020)
Cases of Dengue Hemorrhagic Fever (DHF), filariasis and chikungunya in Indonesia in 2018 carried by Aedes sp and Culex sp are still common. Excessive use of synthetic insecticides and larvicides cause resistance and are toxic to humans. The purpose of this study was to determine the concentration and LC50 values of lenca plant extracts (Solanum nigrum) and papaya seeds (Carica papaya) on the larvae of Culex sp and Aedes sp. The concentration variations used in the test were 0% (control), 0.50%, 1.5% and 2.5%. Total mortality of Culex sp larvae against variations in the concentration of Carica papaya extract (p = 0.373) and Solanum nigrum (p = 0.03). LC 50 extract of Solanum nigrum against Culex sp larvae at a concentration of 1.19%. Total mortality of Aedes sp larvae against variations in the concentration of Carica papaya extract (p = 0.11) and Solanum nigrum (p = 0.00). Carica papaya contains alkaloids which are toxic, proteolytic and inhibit larval growth hormone. Solanin in Solanum nigrum is neurotoxic glycalkaloid which can cause disruption of membrane function.